Tribes and space in the Syro-Arabian ḥarrah as revealed by the Safaitic inscriptions (ca. 1st century bc to ca. 4th century ad) - Macdonald, Michael C. A. (Semitica et Classica, 2020)
Abstract Some 2,000 years ago, the nomadic pastoralists who inhabited the basalt and limestone deserts of what is now southern Syria, northeastern Jordan and northern Saudi Arabia, became literate and covered the rocks with tens of thousands of graffiti. These tell us about their interaction with the landscape, their social structures, relationships with each other and with the settled kingdoms and Roman provinces to the west, and above all their personal feelings. They are like leaves from innumerable diaries and give us insights into their way-of-life, society, and individual emotions which are completely lacking for their urban and rural contemporaries. This article examines the ways these nomads and their social groups interacted with the spaces in which they moved. Abstract Il y a environ 2 000 ans, les pasteurs nomades qui habitaient les déserts basaltiques et calcaires de ce qui est aujourd’hui le sud de la Syrie, le nord-est de la Jordanie et le nord de l’Arabie saoudite, se sont alphabétisés et ont recouvert les rochers de dizaines de milliers de graffitis. Ceux-ci nous parlent de leur interaction avec le paysage, de leurs structures sociales, de leurs relations entre eux et avec les royaumes sédentaires et les provinces romaines à l’ouest, et surtout de leurs sentiments personnels. Ils sont comme les feuilles d’innombrables journaux intimes et nous donnent un aperçu de leur mode de vie, de leur société et de leurs émotions individuelles qui fait complètement défaut à leurs contemporains urbains et ruraux. Cet article examine la manière dont ces nomades et leurs groupes sociaux interagissaient avec les espaces dans lesquels ils évoluaient.